Cognition in organizations - Hodgkinson, Gerard P; Healey, Mark P (Annual review of psychology, 2008)
This article reviews major developments from 2000 to early 2007 in the psychological analysis of cognition in organizations. Our review, the first in this series to survey cognitive theory and research spanning the entire field of industrial and organizational psychology, considers theoretical, empirical, and methodological advances across 10 substantive domains of application. Two major traditions, the human factors and organizational traditions, have dominated cognitively oriented research in this field. Our central message is that the technological and human systems underpinning contemporary organizational forms are evolving in ways that demand greater cooperation among researchers across both traditions. Such cooperation is necessary in order to gain theoretical insights of sufficient depth and complexity to refine the explanation and prediction of behavior in organizations and derive psychologically sound solutions to the unprecedented information-processing burdens confronting the twenty-first century workforce.